Abdominal wall endometriosis from general surgeon perspective: Abdominal wall endometriosis - Mladenović, Aleksandar M; Jovančević, Miljan; Milošević, Zoran (PONS - medicinski časopis, 2021)
Objective. Endometriosis is benign disease which is characterised by the presence of the functional endometrial tissue out of the uterine cavity. Abdominal wall endometriosis (AWE) represents any presence of endometrium in the abdominal wall outside the peritoneal cavity. The aim of the work is to analyze the clinical characteristics and surgical treatment of this condition. Methods.We have analised 14 cases of AWE operated on in our department in period from 01.01.2011. to 12.31.2019. Data were obtained by retrospective analysis of medical histories of operated patients, and were analyzed by the method of descriptive statistic. Results. The average age of patients was 33 (26-41) years. In most patients there was data about previous operations on the lower abdomen (Caesarean section). In the clinical picture the dominant elements were pain and palpabile lesion in all patients. The pain is more often of the non-cyclic type (62,4 %). All patients underwent an ECHO examination. Radical resection (R0) was achieved in most patients, while in one patient R1 resection was involved (7,2%). Recurrence occurred in one patient. Conclusion. Even its relatively rare, AWE can bi significant condition for two reasons. First are difficulties and complications it may create for the patient, and second is that it can be a serious differential diagnostic problem for physicians. In younger patients with palpable and painful lesions in the lower abdomen, and with a history of previous gynecological surgeries, it is necessary to think about AWE in differential diagnosis. Surgery with mandatory histopathological examination is the method of choice in the treatment of AWE. The results of surgical treatment are excellent if sufficient radicality is achieved (R0 resection). Key words: endometriosis, caesarean section, surgical treatment